Urine kidney injury molecule-1 predicts subclinical kidney disease among persons living with HIV initiating tenofovir disoproxil fumarate-based ART in Zambia - Chabala, Freeman W.; Siew, Edward D.; Wester, C. William; Brennan, Alana T.; Phiri, Masauso M.; Vinikoor, Michael J.; Masenga, Sepiso K.; Aliyu, Muktar H. (Frontiers in Nephrology, 2025)
IntroductionAntiretroviral therapy (ART) increases the life expectancy of persons living with HIV (PLWH), but not without potentially serious adverse effects. Tenofovir disoproxil fumarate (TDF) can cause nephrotoxicity, manifesting as acute kidney injury (AKI) that may persist after treatment discontinuation. Kidney injury biomarkers such as kidney injury molecule-1 (KIM-1), retinol-binding protein-4 (RBP-4), interleukin-18 (IL-18), and neutrophil gelatinase-associated lipocalin (NGAL) can aid early diagnosis and predict TDF-associated nephrotoxicity. This study aimed to determine whether the change from baseline in urine KIM-1 (δKIM-1) and NGAL (δNGAL) following 2 weeks of TDF use could predict subclinical TDF-associated nephrotoxicity before the overt manifestation as acute kidney disease after 3 months.MethodsA prospective cohort study of 205 PLWH was conducted at the Adult Center for Infectious Disease Research (AIDC) in Lusaka, Zambia. ART-naïve PLWH who were starting treatment with TDF with intact kidney function [estimated glomerular filtration rate (eGFR)> 60 mL/min/1.73m2] were followed at initiation, 2 weeks, and approximately 3 months to determine the incidence of TDF-associated nephrotoxicity. We measured urine KIM-1 and NGAL at baseline and after 2 weeks of treatment to determine if it predicted subclinical nephrotoxicity. The presence of TDF-associated nephrotoxicity was defined according to the established acute kidney disease and disorders criteria (AKD) as having either 1) one or more episodes of eGFR< 60ml/min/1.73m2 within 3 months, 2) a reduction in eGFR of greater than 35% (from baseline) within 3 months, and/or 3) an increase in serum creatinine of more than 50% (from baseline) within 3 months.ResultsThe incidence of TDF-associated nephrotoxicity was 22%. Baseline eGFR, creatinine, age, female sex, and BMI predicted the risk of overt TDF-associated nephrotoxicity. The median baseline KIM-1-to-creatinine and NGAL-1-to-creatinine ratios of the participants who developed overt TDF-associated nephrotoxicity and those who did not were not significantly different. However, every 1 pg/mg increase in δKIM-1 was associated with a 41% higher risk of TDF-associated nephrotoxicity. No association was observed with δNGAL.ConclusionsThe incidence of TDF-associated nephrotoxicity was high. Change in KIM-1 level within 2 weeks of the initiation of TDF treatment predicted subclinical TDF-associated nephrotoxicity before overt manifestation as acute kidney disease while δNGAL within the same period did not predict subclinical TDF-associated nephrotoxicity.